Transforming Islamic Community Development Da'wah through Psycho-Sufistic Education: TGKH Muhammad Zainuddin Abdul Majid’s Perspective - Hassan Zaeni; Lalu Gede Muhammad Zainuddin Atsani; Fu'ad Zaini (Lembaga Bale Literasi, 2025)
This study discusses the transformation of Islamic community development da‘wah through psychospiritual education from the perspective of TGKH Muhammad Zainuddin Abdul Majid. The study aims to analyze the values of psychospiritual education contained in Wasiat Renungan Masa and its relevance to da‘wah and Islamic community development. This research employed a qualitative approach using the library research method. Data were obtained from Wasiat Renungan Masa, scientific journals, books, and other relevant studies, then analyzed using descriptive-analytical methods. The findings reveal that the psychospiritual education of TGKH Muhammad Zainuddin Abdul Majid emphasizes spiritual development, moral education, and social responsibility. Values such as sincerity, steadfast faith, respect for teachers, the spirit of struggle, and social devotion serve as the foundation for shaping the character of Islamic society. Psychospiritual education is also relevant in addressing moral crises and spiritual degradation in modern society through a transformative da‘wah approach based on education and spirituality.